Uptake of Nitrogen, Phosphorus, and Kalium nutrients in various local rice varieties with various irrigations - Isnawan, Bambang; Aini, Lis Noer; Septiana, Timami Nur; Supangkat, Gatot (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Intermittent irrigation in cultivating rice plants can reduce and save water needs. The study aims to identify NPK nutrient uptake in various kinds of irrigation to select the suitability of local rice varieties in several types of irrigation. The research was conducted in the Experimental Land, Soil, and Plant Nutrition Laboratory and Production Laboratory of the Faculty of Agriculture, University of Muhammadiyah Yogyakarta, for five months. The research method was conducted using a field experiment with a Randomized Complete Block Design (RCBD) of 3 repetitions and a 3 by 4 strip plot layout. Factor I, namely irrigation, includes conventional irrigation (A1), ten days of inundation and five days of drying (A2), and seven days of inundation and three days of drying (A3). Factor II is the rice varieties, including Rojolele Genjah (V1), Pandan Wangi (V2), Mentik Wangi (V3), and Ciherang (V4). The results showed no interaction between the irrigation type and the variety of the observed parameters. Irrigation does not affect the absorption of N, P, and K, but it affects the weight of rice clump grain. Variety influences the uptake of P and K in rice plants. The Pandan Wangi variety has a higher P absorption than other varieties. Rojolele varieties have higher K absorption than Pandan Wangi and Ciherang varieties. The grain weight per rice clump of the Pandan Wangi variety is heavier than that of other varieties. Grain weight per rice clump with 10-day intermittent irrigation: 5-day drying is heavier than conventional irrigation. It is necessary to develop rice cultivation of the Pandan Wangi variety with intermittent irrigation because it does not reduce the absorption of N, P, and K, and the grain per clump is heavier Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 6: Clean Water and SanitationSDG 12: Responsible Consumption and Production